Cornell scale for depression in dementia: Study of residents in a Northern Thai long-term care home - Nahathai Wongpakaran (2018)
Objective a Tis study aimed to analyse the validity of the Tai version of the Cornell Scale for Depression in Dementia (CSDD) when using DSM-IV criteria. Methods A cross-sectional study was carried out of 84 elderly residents in a residential care home setting in Tailand. Te participants went through a comprehensive geriatric assessment which included a Mini-Mental State Examination, a Mini-International Neuropsy-chiatric Interview (MINI) and use of the CSDD tool. A ROC analysis was performed in order to test the validity of the CSDD as against the DSM-IV when used by the MINI. Results ROC analysis revealed a better score for those areas found under the curve for the CSDD-as against the DSM-IV criteria (0.96). With a cut-of score of >6, the CSDD yielded the highest sensitivity score (100%), plus produced a specifcity of 81% and a negative predictive value of 100%. It also had a positive predictive value of 69%. Te validity of the CSDD was found to be better for the group experiencing cognitive impairment than with the non-cognitive impairment group in terms of the agreement of CSDD items between patients and caregivers. Te CSDD yielded a high internal consistency (Cronbach's alpha=0.87). Conclusion CSDD is a valid tool to use for identifying depressive disorders among Tai LTC home residents - those experiencing and those not experiencing cognitive impairment. © 2013 Korean Neuropsychiatric Association.